The Effect of Financial Statement Transparency and Budget Realization Through the Village Website on the Level of Public Trust in Paya Tusam Village - M. Yoga Attoriq; Ayu Kurnia Sari; Yunita Sari Rioni (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze and empirically examine the effect of financial statement transparency and budget realization through the village website on the level of public trust in Paya Tusam Village. The background of this research is based on the importance of transparency and accountability in managing the Village Revenue and Expenditure Budget (APB Desa) to achieve good governance and reduce information asymmetry between the village government and the community. This study uses a quantitative approach with multiple linear regression analysis. The population consists of the residents of Paya Tusam Village, and the data were collected through questionnaires. The independent variables are financial statement transparency and budget realization through the village website, while the dependent variable is public trust. The results are expected to show that financial statement transparency and budget realization have a positive and significant effect on public trust, both partially and simultaneously. This research contributes to improving financial information disclosure practices and strengthening public trust in village fund management.